An Assessment of the Theory-practice Gap in Conflict Transformation and Peace Education: A Focus on Seeds of Peace - Kosik, Agnieszka D. (Université d'Ottawa / University of Ottawa, 2012)
Peace education offers potential for transforming violent conflict into peace between groups in conflict. The research literature on conflict transformation theory and peace education has identified key assumptions for building long-term peace following violent conflict. The extent to which peace education programs have incorporated these theoretical notions, however, is not well known. This thesis explored the extent to which key theoretical insights from the literature on conflict transformation theory and peace education are incorporated in a prominent peace education program, Seeds of Peace. Data collection consisted of interviews with ten program staff members and written documentation produced by Seeds of Peace. Employing the analytical framework developed from a review of the literature, a comparison between theoretical notions and Seeds of Peace programming was done. Findings of this study highlight the extent to which there are gaps between theory and practice, and a case is made for the establishment of a more explicit connection between theory and practice. Furthermore, the thesis highlights the importance of further studies to address the research gap.
Keywords: conflict trasnformation; peace education; identity conflict; seeds of peace; conflict